Antagonistic Activity of Paenibacillus polymyxa against Xanthomonas oryzae: An In Vitro Dual Culture Study - Purwanti, Eny Wahyuning; Ramadhani, Reyhan Destrawan; Farid, Abdul (Jurnal Perlindungan Tanaman Indonesia, 2025)
Bacterial leaf blight (BLB) caused by Xanthomonas oryzae is a major constraint to rice production in Tulungagung, especially in the District of Gondang. This study aimed to evaluate the antagonistic effect of Paenibacillus polymyxa on Xanthomonas oryzae using an in vitro dual culture assay. The experiment was conducted as a randomized complete design with four treatments: P0 (X. oryzae, P1 (X. oryzae + chemical bactericide), P2 (X. oryzae + sterile water), and P3 (X. oryzae + P. polymyxa), each replicated five times. Observations were made for seven days by measuring the diameter of X. oryzae colonies. Data were analyzed using one-way ANOVA and a Duncan Multiple Range Test post-hoc test was done if a significant difference were detected. The analysis showed significant difference among treatments. The application of P. polymyxa (P3) resulted in significantly smaller colony diameters compared to P0 and P2, and was statistically similar to bactericide treatment (P1). These results showed that P. polymyxa is effective in inhibiting the growth of X. oryzae and has strong potential as a biological control agent for sustainable rice cultivation.